2020
DOI: 10.3390/ijms21155419
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profile of TPS Gene Family in Dendrobium officinale and the Role of DoTPS10 in Linalool Biosynthesis

Abstract: Terpene synthase (TPS) is a critical enzyme responsible for the biosynthesis of terpenes, which possess diverse roles in plant growth and development. Although many terpenes have been reported in orchids, limited information is available regarding the genome-wide identification and characterization of the TPS family in the orchid, Dendrobium officinale. By integrating the D. officinale genome and transcriptional data, 34 TPS genes were found in D. officinale. These were divided into four subfamilies (TPS-a, TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
6
39
0
Order By: Relevance
“…Most of the orchid TPSs belong to TPS-a and TPS-b subfamilies (89/115, Table 1). In the TPS-a subfamily, copies from dicot and monocot species formed distinct subgroups, which is in accordance to previous studies [15,16]. However, compared to angiosperm dicot species, which have more TPSs in TPS-a subfamily, orchid (monocot) TPSs have more members in TPS-b subfamily than in TPS-a subfamily.…”
Section: The Evolution Of Tps Genes In Orchidaceae Speciessupporting
confidence: 91%
See 2 more Smart Citations
“…Most of the orchid TPSs belong to TPS-a and TPS-b subfamilies (89/115, Table 1). In the TPS-a subfamily, copies from dicot and monocot species formed distinct subgroups, which is in accordance to previous studies [15,16]. However, compared to angiosperm dicot species, which have more TPSs in TPS-a subfamily, orchid (monocot) TPSs have more members in TPS-b subfamily than in TPS-a subfamily.…”
Section: The Evolution Of Tps Genes In Orchidaceae Speciessupporting
confidence: 91%
“…TPSs in P. equestris and D. officinale have been reported [15,60]. These TPSs are divided into four subfamilies (TPS-a, TPS-b, TPS-c, and TPS-e/f ).…”
Section: The Evolution Of Tps Genes In Orchidaceae Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…To further clarify TPS genes’s potential roles in the turquoise module and the blue module, we generated a phylogenetic tree by neighbor-joining method ( Yu et al, 2020 ). Figure 8 showed that DoTPSs proteins were classified into four different clades, 14 in TPS-a, 16 in TPS-b, 3 in TPS-c, and 1 in TPS-e/f.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified 34 TPS genes in D. officinale . They were classified into four subfamilies (TPS-a, TPS-b, TPS-c, and TPS-e/f) ( Yu et al, 2020 ). In the experiment, the volatile terpenoids in flowers were identified and quantitatively analyzed for two cultivars of Wanhu No.5 and Wanhu No.6 of D. officinale .…”
Section: Introductionmentioning
confidence: 99%